LRET investigations of conformational changes in the ligand binding domain of a functional AMPA receptor - Gonzalez, Jennifer (2008)
The structural investigations using the soluble ligand binding domain of the AMPA subtype of the glutamate receptor have provided invaluable insight into the mechanistic pathway by which agonist binding to this extracellular domain mediates the formation of cation-selective channels in this protein. These structures, however, are in the absence of the transmembrane segments, the primary functional component of the protein. Here, we have used a modified luminescence resonance energy transfer based method to obtain distance changes due to agonist binding in the ligand binding domain in the presence of the transmembrane segments. These distance changes show that the cleft closure conformational change observed in the isolated ligand binding domain upon binding agonist is conserved in the receptor with the channel segments, thus establishing that the isolated ligand binding domain is a good model of the domain in the receptor containing the transmembrane segments.